The potential of the coral species Porites astreoides as a paleoclimate archive for the Tropical South Atlantic Ocean. (August 2017) - Pereira, N.S.; Sial, A.N.; Frei, R.; Ullmann, C.V.; Korte, C.; Kikuchi, R.K.P.; Ferreira, V.P.; Kilbourne, K.H.
Abstract: The aragonitic skeletons of corals are unique archives of geochemical tracers that can be used as proxies for environmental conditions with high fidelity and sub-annual resolution. Such records have been extensively used for reconstruction of climatic conditions in the Pacific and Indian Oceans, Red Sea and Caribbean, but lack for the Equatorial South Atlantic. Here we present coral-based records of Sr/Ca, δ 18 O and δ 13 C and the first δ 18 O–SST calibration for the scleractinian coral species Porites astreoides from the Rocas Atoll, Equatorial South Atlantic. The investigated geochemical proxies for P. astreoides presented a very well-developed seasonal cyclicity in all proxies. We use the monthly means of δ 18 O and SST from the period of 2001–2013 to propose a calibration for a paleothermometer based on Porites, which gives T(°C) = −8.69(±0.79)* δ 18 O −7.05(±3.14), and yielded a SST δ 18 O–depended reconstruction with fidelity better than 0.5 °C for most of the record. Biases of up to 2 °C might be associated with reduced growth rate periods of the coral record. The Sr/Ca data show systematic, annual fluctuations but analyses are too imprecise to propose a Sr/Ca-SST calibration. The δ 13 C values are found to vary in phase with δ 18 O and Sr/Ca and are interpreted to be controlled by solar irradiation-modulated photosynthetic activity on the annual level. Our findings extend the global data base of coral records, contributing to further investigations using coral skeleton as environmental archives. In particular, the present study helps to better understand the climate variability of the South Atlantic tropical ocean-atmosphere system.